A 20.7 kb Deletion within the Factor VIII Gene Associated with LINE-1 Element Insertion - Water, Neil Van de; Williams, Ruth; Ockelford, Paul; Browett, Peter (Thrombosis and Haemostasis, 1998)
Large deletions within the factor VIII gene account for approximately 5% of the mutations causing haemophilia A. The characterization of such mutations can provide insights into the molecular mechanisms of these and other deletions in man. We have analyzed a 20.7 kb deletion spanning exons 15 to 20 within the factor VIII gene in a patient with severe haemophilia A. Long range PCR was used to investigate the extent of the deletion and to provide a template for sequencing across the deletion breakpoint. A 38-base insertion homologous to the 3’ region of a LINE-1 (L1) element was detected at the breakpoint of the deletion. Normal sequence at the 5’ breakpoint in intron 14 was homologous to an L1 flanking region and normal sequence at the 3’ breakpoint in intron 20 was homologous to an adjacent sequence within the same L1 flanking region. A molecular mechanism for the deletion involving retrotransposition of a readthrough product of an L1 element plus its 3’ flanking region is suggested.